Back Cover: Planar‐Chiral Secondary Ferrocenylphosphanes (Eur. J. Inorg. Chem. 02/2017). Issue 2 (6th January 2017) - Pandey, Souvik; Sárosi, Menyhárt B.; Lönnecke, Peter; Hey‐Hawkins, Evamarie
Abstract : This cover feature shows a diastereomerically pure planar‐chiral secondary ferrocenylphosphane derived from Ugi's amine against a background depicting the Head of Janus, a symbol for the two different features of these compounds: They find application as chiral ligands for metal complexes in asymmetric catalysis, and the corresponding phosphinoborane derivatives could be suitable precursors for the synthesis of chiral P–B polymers by dehydrocoupling. Details are discussed in the article by E. Hey‐Hawkins et al. on page 256 ff (DOI: 10.1002/ejic.201600935 ).